ANALYZING SELF-SUFFICIENCY OF SANTRI: A DESRIPTIVE STUDY OF PESANTREN UMMUL MUKMININ SOUTH SULAWESI - Darmawati Darmawati (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to find out how to foster the self-sufficiency of students at the Ummul Mukminin 'Aisyiyah Islamic Boarding School for the South Sulawesi Region. It also explores what kind of student’s self-sufficiency. The research used a descriptive qualitative method approach, namely the data collected through informants' answers were selected and sorted which were then analyzed semantically. The results showed that the orientation of fostering the self-sufficiency of students at the Islamic Boarding School for Puteri Ummul Mukminin 'Aisyiyah in the South Sulawesi Region was directed at 2 aspects, namely physical and spiritual aspects. These two aspects will be well-formed if they are carried out with good and consistent management and are fully supported by the parents of the students themselves.